STAGES OF LAND PROCUREMENT FOR PUBLIC INTEREST DEVELOPMENT (STUDY OF DECISION NO.227/PDT/G/2020/PN.MDN) - Cindy Situmeang; Gunawan Djajaputra (Jurnal Hukum Adigama, 2022)
Land Procurement for the Implementation of Development in the Public Interest is one of the manifestations of the social function of land rights which has been mandated in Article 6 of the LoGA. appropriate compensation for the land rights without compromising the rights and sense of justice. This includes the interests of the government as well as justice for the rights of the people who are taken and also the public interest in using the facilities built by taking the land of the land owner with the power of his Land Rights. The research method used is a literature study that uses Court Decisions and primary & secondary sources of material as research support. The position of a person in a lawsuit complaint is also very important, in this case the judge's consideration is also needed in viewing a lawsuit, and also for the government, it must provide the right of compensation in kind. The results of this literature study research method state that land acquisition for development is in the public interest to uphold the basic principles of humanity and justice.